A Holistic Mentoring Management by Homeroom Teachers in Shaping the Character of High School Students in Ketapang Regency - Dedy Sadar Setyawan; Mada Sutapa (Journal of Education and Teaching Learning, 2026)
This study is motivated by the importance of strengthening character education through holistic mentoring amid the increasing complexity of adolescent behavior and the challenges of school culture at the senior high school level. The study aims to analyze the management of holistic mentoring by homeroom teachers in shaping the character of high school students in Ketapang Regency. This research employed a qualitative approach with an interpretive paradigm and a multi-case study design conducted at SMAN 3 Ketapang, SMAN 1 Nanga Tayap, and SMAN 1 Simpang Hulu. Data were collected through in-depth interviews, participatory observation, and documentation, then analyzed using the interactive model of Miles, Huberman, and Saldaña. The results show that homeroom teachers play a strategic role as social, emotional, and moral mentors for students through interpersonal communication, role modeling, and a positive school culture. The findings also indicate that the effectiveness of character building is influenced by school culture, family collaboration, and the school’s socio-geographical context. The study concludes that holistic mentoring based on a positive school culture is capable of strengthening students’ character formation in a contextual and sustainable manner.